Assessing COVID IGRA and IgG antibodies in healthcare workers post vaccination - Lina Ghandour; Wissam Yaacoub; George F Araj (Journal of Infection in Developing Countries)
Introduction: This study evaluated the durability of humoral and cell-mediated immunity (CMI) post Pfizer vaccination among healthcare workers (HCWs) at a tertiary care center in Lebanon.